Collaboration and the Emerging Craft Brewing Industry: An Exploratory Study. Issue 3 (3rd July 2018) - Alonso, Abel Duarte; Alexander, Nevil; O'Brien, Seamus
ABSTRACT: In adopting various elements associated with the theory of collaboration, this exploratory study investigates collaboration in the context of predominantly micro- and small craft breweries. The findings revealed that collaboration within other brewers helped increase product quality, gain basic knowledge of new recipes, and enhance strategic knowledge about the industry. The applicability of the elements related to the theory of collaboration was confirmed. For instance, the element of stakeholders of a problem domain was aligned with the notion that craft brewery operators' actions, including collaboration, can have significant impacts on the problem domain that brought them together.